ISSP 2016 - Role of government IV: Sweden - ISSP 2016 - Role of government V: Sweden - Edlund, Jonas (Umeå University, 2018)
This survey is the Swedish part of the 2016 'International Social Survey Program' (ISSP), and it is the third time Sweden participates in an ISSP-survey focusing on the role of government. The earlier studies with this theme were conducted in 1996 and 2006.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 2016 is focussing on the role of government.

Denna undersökning ingår som den svenska delen i 2016 års undersökning i 'International Social Survey Program' (ISSP) och det är den tredje gången Sverige ingår i en ISSP-undersökning fokuserad på temat den offentliga sektorn. De tidigare undersökningarna med detta tema genomfördes 1996 och 2006.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 2016 undersöker åsikter om politik och den offentliga sektorn.
ISSP 2016 - Åsikter om politik och den offentliga sektorn
Keywords: public sector; offentlig sektor; employment; anställning; cultural identity; kulturell identitet; religious attendance; religiöst deltagande; public expenditure; offentlig utgift; political extremism; politisk extremism; voting; röstning; political interest; politiskt intresse; public services; offentlig service; taxation; beskattning; political participation; politiskt deltagande; marital status; civilstånd; education; utbildning; religious affiliation; religiös tillhörighet; corruption; korruption; public administration; offentlig förvaltning; households; hushåll; political attitudes; politiska åsikter; national security; nationell säkerhet; counterterrorism; skydd mot terrorism; Political behaviour and attitudes; Politiska beteenden och attityder; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi